DCDR Spectroscopy as Efficient Tool for Liposome Studies: Aspect of Preparation Procedure Parameters. Issue 5 (11th July 2012) - Kočišová Kočišová, E. E.; Vodáková Vodáková, A. A.; Procházka Procházka, M. M.
Abstract : Drop-coating deposition Raman (DCDR) spectroscopy was employed to study liposome suspensions. The method is based on a specific drying process on the hydrophobic surface that efficiently accumulates the macromolecular sample in a ring of the edge of the dried drop. We studied liposome suspensions purchased from two sources (Avanti Polar Lipids, Inc. and Sigma-Aldrich, Co.) and prepared under different conditions. Structure of the dried drop substantially depends on the lipid concentration, lipid composition of the sample, and used solvent. Optimal lipid concentration is about 0.3 mg/ml in all cases, asolectin and DSPC suspensions form compact dried drops when dissolved in water and phosphate buffer, respectively. Drying process of the sample drop does not influence the initial phase state (gel or liquid-crystalline) of the studied liposomes excepting DSPC from Sigma-Aldrich, Co.